Gastroprotective mechanism of Bauhinia thonningii Schum - Siddig Ibrahim Abdelwahab; Manal Mohamed Elhassan Taha; Mahmood Ameen Abdulla; Norazie Nordin; A.Hamid A.Hadi; Syam Mohan; Jaime Jacqueline Jayapalan; Onn Haji Hashim (Elsevier, 2024)
Volume 148 Issue 1